Rejection Sensitivity and Psychological Capital as the Mediators Between Attachment Styles on Social Networking Sites Addiction - Shan, Huanhuan; Ishak, Zahari; Li, Jingyi (Frontiers in Education, 2021)
This study was based on the framework of attachment, reinforcement sensitivity, and positive psychology theories. The main objective is to investigate the rejection sensitivity and psychological capital as the mediators between attachment styles on social networking sites addiction. The sample comprised of 607 college students and the data was collected using an online survey owing to the rapid development and penetration of social networking sites in China. Result demonstrated that there is a mediating effect between rejection sensitivity, psychological capital and attachment styles, on social networking sites addiction. Moreover, insecure attachment styles significantly and negatively predicted on social networking sites addiction. It increased social networking sites addiction via a negative impact on participants’ rejection sensitivity. Furthermore, attachment styles also influence the social networking sites addiction due to its dual effect on rejection sensitivity and psychological capital. Overall, the findings suggest that weakening rejection sensitivity, and enhancing psychological capital can be considered in future studies as contributors to social networking sites addiction for prevention or intervention studies.